Post-colonoscopy colorectal cancers in average-risk Korean subjects with a normal initial colonoscopy - Lee, Han Hee; Kim, Seung Kyoung; Choi, Hyun Ho; Kim, Hyung-Keun; Kim, Sung Soo; Chae, Hiun-Suk; Cho, Hyunjung; Cho, Young-Seok (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: There are relatively few studies regarding the incidence of post-colonoscopy colorectal cancer (PCCRC) in Asian countries. We evaluated the characteristics of PCCRC in average-risk Korean subjects. Materials and Methods: This study included subjects who were ≥50 years of age and had undergone a first completed colonoscopy between January 2001 and December 2004, at which no baseline adenoma had been detected, followed by a second colonoscopy 1–5 years later. The incidences and characteristics of advanced neoplasia in these subjects were assessed. Results: A total of 343 subjects underwent follow-up colonoscopy within 5 years. Seventy-three (21.3%) subjects were found to have at least one adenoma on follow-up colonoscopy. Advanced adenoma was found in eight (2.3%) subjects, and non-advanced adenomas were found in 65 (19.0%). Five (1.5%) subjects were diagnosed with invasive CRC following a normal colonoscopy. The putative reason for PCCRCs was missed lesions in two (40.0%) subjects and a new cancer in three (60.0%). Conclusion: The risk of advanced neoplasia (including PCCRCs) within 5 years after a normal baseline colonoscopy in our cohort was not low. Considering that 40% of PCCRCs were attributable to missed lesions, our results emphasize the need for technical improvement of colonoscopic examinations to improve adenoma detection.